A relação entre estilo de vida e experiências de consumo: o estudo de caso da marca Gang - Callegaro, Ana Rita Catelan (2012)
During the 1980s, in line with studies focusing on consumer behavior, Holbrook and Hirschman (1982) has stressed the need to abandon the traditional view of marketing, based on the individual as a rational decision maker is to emphasize other aspects inherent consumption. The authors began to question the hegemony of the traditional marketing that might neglect other phenomena important to understanding the perspective of the consumer. These phenomena include recreational activities for leisure, sensory pleasure, aesthetic pleasure and emotional responses. The "experiential view" proposed by the authors was characterized by a flow of fantasies, feelings, and fun associated with the consumption process, which, in turn, presented a variety of subjective aspects - the multiplicity of symbolic meanings, hedonic responses and aesthetic criteria. This paper presents a qualitative and quantitative research through a case study of brand Gang to analyze the convergent and divergent aspects of lifestyle and consumer experiences through the following objectives: to describe the experience of consumption proposed by the company, analyze the dimensions of experience worked for the company and identify the lifestyle consumer brand. The results provided a better understanding on the subject, by building relations between the two themes, namely, the proposed brand experience adapts to the interests of your audience. One of the points that confirm this relationship is the connection between the main activities, interests and opinions of consumers with the brand experience of the proposed Gang. It is understood based on the results that the Gang can be considered a brand focused on the lifestyle of its consumers, since their policy of offering retail adapts to the lifestyle of its consumers. Finally, we present the academic and managerial contributions of the study, as well as its limitations and suggestions for future studies.